"Basically, I look at it like combat": Reflections on moral injury by parents involved with child protection services. (November 2017) - Haight, Wendy; Sugrue, Erin; Calhoun, Molly; Black, James
Abstract: This study considers any "moral injury" occurring among parents involved with the Child Protection System (CPS). Moral injury refers to the lasting psychological, spiritual and social harm caused by one's own or another's actions in a high stakes situation that transgress deeply held moral beliefs and expectations. The existing literature focuses on military contexts, but moral injury also may play a role in increasing the vulnerability of CPS clients who are threatened with loss of their parental rights and dissolution of their families. We administered a modified version of the Moral Injury Events Scale (MIES) (Nash et al., 2013) to 10 CPS involved parents. We then conducted in-depth, semi-structured, audio recorded individual interviews with parents to elaborate their responses to the MIES. Parents' MIES scores and interview elaborations suggest that some CPS-involved parents do experience moral injury. Moral injury was reported as a result of their own parenting behaviors, but also as a result of parents' involvement with professionals and within social systems that are charged with providing assistance to struggling families. For instance, some parents perceived professionals to be shaming, social services to be harmful and legal proceedings stigmatizing. Parents' reported reactions to morally injurious events included lasting feelings of guilt, shame and anger; and loss of trust in professionals. These responses impeded their perceived abilities to fully engage in services. If involvement in CPS places parents at increased risk of moral injury, then moral injury is a critically important construct for child welfare policy makers and workers to understand and address in the conduct of effective, ethical child welfare practice. Highlights: This study considers moral injury among parents involved with Child Protection. Moral injury resulted from parenting behaviors and involvement with CP professionals. Parents' reactions to morally injurious events included guilt, shame, and anger. Parents' responses impeded their abilities to fully engage in services. Moral injury is an important construct for effective, ethical child welfare practice.